Web design : flashfolios. - Wiedemann, Julius, ....- (Hong Kong : Taschen)
Following up on the success of Web Design: Portfolios, this volume features the Internet's best examples of artists, design studios, photographers, designers, and corporations that use Flash to showcase their creations. What once existed only in printed form is increasingly being featured online via dynamic, animated Flash-powered sites. Flashfolios contains a selection of such websites developed exclusively using Flash, demonstrating the sophistication and range of interactive web design today.